A Humanized Mouse Strain That Develops Spontaneously Immune-Mediated Diabetes - Luce, Sandrine; Guinoiseau, Sophie; Gadault, Alexis; Letourneur, Franck; Nitschke, Patrick; Bras, Marc; Vidaud, Michel; Charneau, Pierre; Larger, Etienne; Colli, Maikel L.; Eizirik, Decio L.; Lemonnier, François; et al. (Frontiers in Immunology, 2021)
To circumvent the limitations of available preclinical models for the study of type 1 diabetes (T1D), we developed a new humanized model, the YES-RIP-hB7.1 mouse. This mouse is deficient for murine major histocompatibility complex class I and class II, the murine insulin genes and expresses as transgene the HLA-A*02:01allele, the diabetes high susceptibility HLA-DQ8A and B alleles, the human insulin gene and, in insulin-secreting cells, the human co-stimulatory molecule B7.1. It develops spontaneous T1D along with CD4+ and CD8+ T-cells responses to human preproinsulin epitopes. Most of the responses identified in these mice were validated in T1D patients. This model is amenable to characterization of hPPI-specific epitopes involved in T1D and to the identification of factors that may trigger the autoimmune response to insulin-secreting cells in human T1D. It will allow evaluating peptide-based immunotherapy that may directly apply to T1D in the human and complete preclinical model availability to address the issue of the clinical heterogeneity of the human disease.